Comic Media Impact: Improving Reading Science Literacy Through Exciting Adventures in Picture Worlds - Nur Azmi Alwi; Alami Fitria; Lissa Adlini; Thasya Dwi Hendri Yenni (Postgraduate, University of Mataram, 2024)
This study investigates the impact of comic media on improving science literacy in elementary school students. A quasi-experimental design was used with two groups: an experimental group utilizing comic media and a control group employing traditional methods. Pretest and posttest assessments measured students' reading abilities in science. A t-test analysis was performed to compare the groups' performances. The findings indicate that students exposed to comic media showed significant improvement in reading abilities compared to those in the control group. These results suggest that comic media not only enhances student interest in learning but also improves information retention. The study recommends integrating comic media into the primary school curriculum to effectively boost students' science literacy